Sustainable development, degrowth, Buen Vivir: Voices from Latin America and Spain - Lisocka-Jaegermann, Bogumiła (Studia Ecologiae et Bioethicae, 2019)
The first part of the text deals with critical approaches to development as well as with inconsistencies and contradictions in official, institutional conceptualisations of sustainable development, as indicated by numerous representatives of critical trends. The second part is devoted to attempts to merge sustainability into a critical discourse. Differences between ‘soft sustainability’ in the official mainstream discourse and ‘strong’ and ‘very strong’ ones within transition initiatives developed by both academic and social activists are discussed. Examples of the latter, such as Buen Vivir and degrowth coming mainly from Spanish-speaking countries, are presented.